Nas marés da vida: histórias e Saberes das mulheres marisqueiras - Dantas, Vanda Maria Campos Salmerson (2010)
The harsh reality of women in the municipality of Indiaroba enlarges to much more from everyday household . Every day, they need courage and determination to adentrarem in mangrove cross functional seafood, which sold, ensure their survival. The life of catadoras seafood, fishing in mangrove and have your family's work, is the object of this study, through which search will be highlighted the history of women who perform a subsistence activity in your daily life. Will reflect on their work in the environment into which are entered, the vision that have labour, environment, family, sexuality, and their social relations. The research p Espírito Santo, in which these women, forgetting seafood calls, play activities diversified in its role of being a woman, reason personal awareness, generating an academic curiosity to know their life stories. Through ethnographic method, which spans observations, interviews, workshops and testimonials, we have tried to learn more about the daily life of forgetting seafood. This gives visibility to the human condition in one of its expressions which can help you understand and appreciate the cultural diversity of knowledge and knowledge constructed this activity pecheurfalco